Physiological and Agronomic Responses of Four Rice Varieties to Drought in the Rainforest - Fofana, M.; Sakariyawo, O.S.; Popogbe, M.O.; Oyekanmi, A.A.; Azeez, J.O.; Adegbehingbe, F.T. (University of Agricultural Sciences and Veterinary Medicine Cluj-Napoca, 2018)
The present investigation tested the hypothesis that there would be variation in physiological responses to water deficit among rice varieties from different production ecologies, with contrasting tolerance to water deficit under repeated cycle of soil moisture deficit, at reproductive growth stage. A screen house and a field trial were conducted at International Institute of Tropical Agriculture, Ibadan and Ikenne (Latitude 6° 52' N, Longitude 3° 43' E) respectively. Both experiments had rice varieties ('IR 64', 'WAB 56-104', 'IR 77298-1-2-B-10' and 'NERICA 4') and stress status (stress and control) as treatment factor's, arranged in a randomised complete block design with three replicates. In both trials, the physiological mechanism that underpins varietal differences with repeated cycles of water deficit at the reproductive growth stage was more balanced water status, improved foliar characters, efficient photosynthetic capacity and higher grain yield in comparatively drought tolerant upland rice varieties ('NERICA 4' and 'WAB 56-104'), as opposed with the results for the drought susceptible cultivar 'IR 64'. A converse pattern was observed on water stressed rice, despite fewer cycles of water deficit on the field. The results could have suggested that the initiation of water deficit is the rate limiting step rather than its intensity at the reproductive growth stage.